The bidirectional relationship between sleep and physical activity following traumatic brain injury. (15th March 2021) - Bruijel, Jessica; van Heugten, Caroline M.; Murray, Jade; Grima, Natalie; Ymer, Lucy; Walters, Elizabeth M.; Sinclair, Kelly; Stapert, Sven Z.; Vermeeren, Annemiek; Ponsford, Jennie L.
Abstract: Sleep and physical activity are both modifiable behavioural factors that are associated with better health and are potentially related. Following traumatic brain injury, damage to the brain caused by an external force, sleep disturbances are common. Exploring bidirectional relationships between sleep and physical activity might provide insight into whether increasing physical activity could decrease these sleep disturbances. The current study, therefore, examined inter‐ and intra‐individual temporal associations between sleep and daytime physical activity in 64 people with traumatic brain injury reporting sleep problems or fatigue (47 males; mean age, 40 years). Sleep and physical activity were measured using actigraphy with corroborating sleep diaries over 14 consecutive days. Multilevel models were used to examine inter‐ and intra‐individual associations between physical activity and sleep. Inter‐individual variations showed that earlier bedtimes, earlier wake‐up times and lower sleep efficiency were associated with more physical activity. Intra‐individual temporal variations showed no significant association of daytime physical activity with sleep duration or continuity. However, shorter sleep time and less wake after sleep onset than usual were associated with more time spent in light‐intensity activity the next day. Therefore, sleep may have more of an influence on physical activity than physical activity has on sleep in people with traumatic brain injury. In conclusion, the results do not confirm a potential beneficial effect of physical activity on sleep but suggest that improving sleep quality might be relevant to support of a physically active lifestyle in people with traumatic brain injury. Further research is necessary to confirm these results.